Simvastatin Restored Vascular Reactivity, Endothelial Function and Reduced String Vessel Pathology in a Mouse Model of Cerebrovascular Disease. Issue 3 (March 2015) - Tong, Xin-Kang; Hamel, Edith
Cerebrovascular dysfunction seen in Alzheimer's disease (AD) and vascular dementia (VaD) is multifaceted and not limited to the amyloid-β (Aβ) pathology. It encompasses structural alterations in the vessel wall, degenerating capillaries (string vessels), vascular fibrosis and calcification, features recapitulated in transgenic mice that overexpress transforming growth factor-β1 (TGF mice). We recently found that simvastatin rescued Aβ-mediated cerebrovascular and cognitive deficits in a transgenic mouse model of AD. However, whether simvastatin can counteract Aβ-independent deficits remains unknown. Here, we evaluated the effects of simvastatin in aged TGF mice on cerebrovascular reactivity and structure, and on cognitive performance. Simvastatin restored baseline levels of nitric oxide (NO), NO-, and KATP channel-mediated dilations and endothelin-1-induced contractions. Simvastatin significantly reduced vasculopathy with arteriogenic remodeling and string vessel pathology in TGF mice. In contrast, simvastatin did not lessen gliosis, and the cerebrovascular levels of pro-fibrotic proteins and calcification markers remained elevated after treatment. The TGF mice displayed subtle cognitive decline that was not affected by simvastatin. Our results show potent benefits of simvastatin on endothelial- and smooth muscle cell-mediated vasomotor responses, endothelial NO synthesis and in preserving capillary integrity. We conclude that simvastatin could be indicated in the treatment of cerebrovascular dysfunction associated with VaD and AD.